Synthesis of novel β-carboline derivatives with potential antimicrobial and anti helminthic activities - G. Swetha; M. Prathyusha; Santhosh pawar V. B. Snigdha (International Journal of Pharmacy and Analytical Research, 2015)
Synthesis of novel heterocyclic compounds containing the β-carboline moiety, which have a valuable biological activities, has been achieved through the nucleophilic substitution of tryptamine to N’-(2-(1H indo-3yl)ethyl) ethane1,2 diamine (I) followed by the cyclocondensation to the corresponding β-carboline derivatives (IV-IX). Isolated yields in the range of 50-80% were obtained. The structures of the newly synthesized compounds were elucidated by spectroscopic data. All the compounds were screened for the antibacterial and antihelminthic activities using streptomycin and albendazole as standard drugs.